Foreign exchange option pricing : a practitioner's guide - Clark, Iain J. (Chichester, West Sussex, U.K. : Wiley, 2011)
This book covers foreign exchange options from the point of view of the finance practitioner. It contains everything a quant or trader working in a bank or hedge fund would need to know about the mathematics of foreign exchange-not just the theoretical mathematics covered in other books but also comprehensive coverage of implementation, pricing and calibration. With content developed with input from traders and with examples using real-world data, this book introduces many of the more commonly requested products from FX options trading desks, together with the models that capture the risk c.
A gentle introduction to FX markets -- Mathematical preliminaries -- Deltas and market conventions -- Volatility surface construction -- Local volatility and implied volatility.
Includes bibliographical references (pages 265-270) and index.
Print version record.
Keywords: Options (Finance) -- Prices; Stock options; Foreign exchange rates; Foreign exchange rates; Options (Finance) -- Prices; Stock options; BUSINESS & ECONOMICS -- Foreign Exchange; Foreign exchange rates; Options (Finance) -- Prices; Stock options; Electronic books